1999
DOI: 10.1210/jcem.84.9.6003
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroepiandrosterone Sulfate Enhances Natural Killer Cell Cytotoxicity in Humans Via Locally Generated Immunoreactive Insulin-Like Growth Factor I1

Abstract: Experimental and clinical investigations suggest the hypothesis that dehydroepiandrosterone sulfate (DHEAS) can positively influence natural killer (NK) immunity via locally produced insulin-like growth factor I (IGF-I) from NK cells. In the present study, the NK cell cytotoxicity (NKCC) and IGF-I levels in the supernatant of NK cells were studied at baseline and after exposure to various molar concentrations of DHEAS (from 10(-5)-10(-8) mol/L x mL/7.75 x 10(6) NK cells) in healthy subjects of young and old ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 58 publications
0
8
1
1
Order By: Relevance
“…DHEA has been demonstrated as a strong parasiticidal molecule in several systems. In another study, exogenous DHEA administration was shown to upregulate the immune system, specifically the cellular immune response, by increasing the number and function of natural killer cells [25]. However, our findings do not support this notion since IL-2 mRNA levels do not change in response to DHEA treatment [16].…”
Section: Dehydroepiandrosteronecontrasting
confidence: 81%
“…DHEA has been demonstrated as a strong parasiticidal molecule in several systems. In another study, exogenous DHEA administration was shown to upregulate the immune system, specifically the cellular immune response, by increasing the number and function of natural killer cells [25]. However, our findings do not support this notion since IL-2 mRNA levels do not change in response to DHEA treatment [16].…”
Section: Dehydroepiandrosteronecontrasting
confidence: 81%
“…An alternative mechanism of action of the steroids is suggested by Solerte et al who studied the effects of DHEAS on the natural killer activities of purified human NK cells. The increase in NK activity seen with DHEAS in vitro was dose-dependent and correlated with the amount of insulin like growth factor 1 (IGF-1) released to the supernatant under a variety of conditions [174], suggesting that the effects of DHEAS may have been mediated by IGF-1. Ueda et al have postulated another novel plasma membrane receptor for DHEAS, showing evidence supporting DHEAS activation of a sub-type of sigma receptor on macrophages, causing histamine release and a nociceptive stimulus [175].…”
Section: Other Potential Molecular Mechanisms Of Dhea(s) Actionmentioning
confidence: 99%
“…DHEA administration to rodents increases IL-2 secretion (13) and natural killer (NK) cell cytotoxicity (14 -16) and decreases circulating IL-6 (17). Similarly, in vitro studies employing human immune cells show a DHEA-induced increase in IL-2 secretion (18) and NK cell cytotoxicity (19) and conversely an inhibition of IL-6 release (20). It is unclear to what extent these immune effects are due to direct effects of DHEA or mediated via downstream conversion to other steroids including the DHEA metabolites androstenediol and androstenetriol (Fig.…”
mentioning
confidence: 99%